A new genus of Eunotiales (Bacillariophyta, Bacillariophyceae: Peroniaceae), Sinoperonia, from Southeast Asia, exhibiting remarkable phenotypic plasticity with regard to the raphe system. Issue 2 (1st March 2018) - Liu, Yan; Kociolek, John P.; Glushchenko, Anton; Kulikovskiy, Maxim; Fan, Yawen
Abstract: We describe Sinoperonia gen. nov . for freshwater diatoms from mountainous regions of south-central China and northern Vietnam, whose single species, S. polyraphiamorpha sp. nov ., develops monoraphid, biraphid and araphid frustules in the general proportions of 4:2:1 (China) or 2:1:1 (Vietnam), respectively, in different populations. Light and scanning electron microscope observations of this species show that raphe-bearing valves also have rimoportulae, and thus it is assigned to the Eunotiales. The raphe-bearing valves have the raphe at or near the middle of the valves, suggesting a placement in the Peroniaceae, and this new diatom is compared with the two other genera, Peronia and Actinellopsis, in this small but phylogenetically important group. We discuss the extreme morphological variation in this new taxon, and the growing body of evidence that the freshwater diatom flora of Southeast Asia may harbour many endemic genera as well as species.